Aerobactin Seems To Be a Promising Marker Compared With Unstable RmpA2 for the Identification of Hypervirulent Carbapenem-Resistant Klebsiella pneumoniae: In Silico and In Vitro Evidence - Shankar, Chaitra; Basu, Soumya; Lal, Binesh; Shanmugam, Sathiya; Vasudevan, Karthick; Mathur, Purva; Ramaiah, Sudha; Anbarasu, Anand; Veeraraghavan, Balaji (Frontiers in Cellular and Infection Microbiology, 2021)
Background:The incidence of hypervirulent (hv) carbapenem resistant (CR) K. pneumoniae (Kp) is increasing globally among various clones and is also responsible for nosocomial infections. The CR-hvKp is formed by the uptake of virulence plasmid by endemic high-risk clones or by the uptake of plasmids carrying antimicrobial resistance genes by the virulent clones. Here we described CR-hvKp from India belonging to high risk clones that have acquired virulence plasmid and are phenotypically unidentified due to lack of hypermucoviscosity. Methods:Twenty seven CRKp isolates were identified to possess rmpA2 by whole genome sequencing and resistance and virulence determinants were characterized. By in-silico protein modeling (and validation), protein backbone stability analysis and coarse-dynamics study, the fitness of RmpA, RmpA2 and aerobactin associated proteins- IucA and IutA were determined to establish a reliable marker for clinical identification of CR-hvKp. Results:The CRhvKp belonged to MDR high risk clones such as CG11, CG43, ST15 and ST231 and carried OXA-232 as the predominant carbapenemase followed by NDM. The virulence plasmid belonged to IncHI1B replicon type and carried frameshifted and truncated rmpA and rmpA2. This resulted in a lack of hypermucoviscous phenotype. However, functional aerobactin was expressed in all high-risk clones. In-silico analysis portrayed that IucA and IutA were more stable than classical RmpA. Furthermore, IucA and IutA had relatively lower conformational fluctuations in the functional domains than the non-functional RmpA2 which increases the fitness cost of the latter for its maintenance and expression among CR-hvKp. Hence, RmpA and RmpA2 are likely to be lost among CR-hvKp owing to the increased fitness cost while coding for essential antimicrobial resistance and virulence factors. Conclusion:Increasing incidence of convergence of AMR and virulence is observed among K. pneumoniae globally which warrants the need for reliable markers of identifying CRhvKp. The presence of non-functional RmpA2 among high risk clones highlights the significance of molecular identification of CR-hvKp. The negative string test due to non-functional RmpA2 among CR-hvKp isolates challenges phenotypic screening and faster identification of this pathotype. This can potentially be counteracted by projecting aerobactin as a stable, constitutively expressed and functional marker for rapidly evolving CR-hvKp.